القيم الإسلامية وأثرها في تعديل سلوك التلاميذ من وجهة نظر المعلمين القيم الإسلامية وأثرها في تعديل سلوك التلاميذ من وجهة نظر المعلمين : "دراسة مقرر التربية الإسلامية للصف التاسع بمدنية طرابلس-ليبيا-نموذجا / نجاة نوري "نصير. - Najat Nuri Nusir
This study aims to know how the prescribed Islamic text books for ninth class of the basic education includes a set of Islamic values. It also aims to know how to achieve Islamic values whether they are direct and clear or indirect which are included in the prescribed Islamic text books according to teachers’ viewpoints. The study aims to know the relation between the Islamic values of Islamic text books and students’ conducts. One of the objectives of this study is to determine how effective the demographic variables are, such as( age- sex- qualification – experience). The field of study will be the teachers who teach the prescribed Islamic text books for ninth class of the basic education in (2010-2011) in the capital of Libya (Tripoli), and the sample will be chosen randomly at the rate of 60% from Tripoli schools. In order to achieve the objectives of the study, the researcher used questionnaire as a method of this study which was set depending on previous studies. In addition, this method was developed and modified to be fit for this study. The questionnaire consists of (55) items divided into three sections as the following: First section: it is about the general objectives of prescribed Islamic text books for ninth class of the basic education. Second section: it is about the special objectives of prescribed Islamic text books. Third section: It is about to determine and restrict the Islamic values in prescribed Islamic text books. Furthermore, the researcher will analyze data using statistical methods which is called ( statistical package for the social sciences) using the following steps( honest- steadinessdistinction). Then, the researcher will use factor analysis to reduce and sum up the variables in fewer factors and the researcher also will conduct the rest of the statistical analysis using the following methods( arithmetic average- correlation coefficient-contrast analysis for multi variables(anova).